Evaluating the potential of the microwave hydrothermal method for valorizing food waste by producing 5-hydroxymethylfurfural. (15th December 2021) - Meng, Yanjun; Zhou, Ying; Shao, Yuchao; Zhou, Dan; Shen, Dongsheng; Long, Yuyang
Graphical abstract: Highlights: MHT is an environmentally-friendly food waste valorizing method. The highest HMF yield from food waste could amount to 4.61 wt%. Resource productivity for food waste valorization by MHT was the highest. Abstract: 5-Hydroxymethylfurfural (HMF) is a platform compound with a high added value derived from biomass. In this study, microwave hydrothermal treatment (MHT) was used to produce HMF from food waste (FW). By optimizing the holding temperature (230 °C) and the holding time (15 min), an HMF yield of 4.61 wt% was obtained, the highest value yet achieved. The main HMF precursors exhibited different phenomena: the fructose content decreased as the holding temperature and holding time increased, while the glucose content first increased then decreased. It was proved that the potential profit of HMF production from FW by MHT was 10, 674 USD/tonne, and the resource productivity was 60 to 1000 times that of other valorization methods. MHT is a feasible strategy for valorizing FW by producing the high added value product, HMF.